Islam Jawa dan Akulturasi Budaya: Karakteristik, Variasi dan Ketaatan Ekspresif - Sumbulah, Umi (UIN Maulana Malik Ibrahim Malang, 2012)
Javanese Islam has a character and a unique religious expressions. This is because the spread of Islam in Java, more dominant takes the form of acculturation, both absorbing and dialogical. The pattern of Islam and Javanese acculturation, as well as can be seen on the expression of the Java community, is also supported by the political power of Islamic kingdom of Java, especially Mataram which had brought Islam to the Javanese cosmology Hinduism and Buddhism. Although there are f luctuations in the relation of Islam to the Javanese culture, especially the era of the 19th century, but the face looks acculturative Javanese Islam dominant in almost every religious expressions Muslim communities in this region, so the aspect of ”syncretic” and tolerance of religions into one distinctive cultural character of Javanese Islam. Agama Islam di Jawa memiliki karakter dan ekspresi keberagamaan yang unik. Hal ini karena penyebaran Islam di Jawa, lebih dominan mengambil bentuk akultrasi, baik yang bersifat menyerap maupun dialogis. Pola akulturasi Islam dan budaya Jawa, di samping bisa dilihat pada ekspresi masyarakat Jawa, juga didukung dengan kekuasaan politik kerajaan Islam Jawa, terutama Mataram yang berhasil mempertemukan Islam Jawa dengan kosmologi Hinduisme dan Budhisme. Kendati ada fluktuasi relasi Islam dengan budaya Jawa terutama era abad ke 19-an, namun wajah Islam Jawa yang akulturatif terlihat dominan dalam hampir setiap ekspresi keberagamaan masyarakat muslim di wilayah ini, sehingga ”sinkretisme” dan toleransi agama-agama menjadi satu watak budaya yang khas bagi Islam Jawa.